Kualitas Pelayanan Pendidikan: Perspektif Pembagian Tugas dan Pengawasan: Kualitas Layanan Pendidikan: Perspektif Pembagian Tugas dan Supervisi - Isyanto, Nur; Akhirudin, Muhamad Towil; Hadi, Riswan (Yapilin Press, 2025)
This study aims to examine the effect of task division and supervision on the quality of educational services at the Hudatul Falah Foundation, Ciseeng, Bogor Regency. Using a quantitative approach with a correlational method, this study involved all teachers at the foundation, with a sample size of 60 respondents. Data were collected through a questionnaire that measured three main variables: task division, supervision, and quality of educational services. The results of the regression analysis showed that task division had a significant effect on service quality with a correlation coefficient of 0.859 and a determination coefficient of 0.738. Supervision also had a significant effect with a correlation coefficient of 0.740 and a determination coefficient of 0.548. The combination of the two showed a very strong effect on service quality, with a correlation coefficient of 0.881 and a determination coefficient of 0.776. These findings indicate that clear management of task division and effective supervision can improve the quality of educational services, making a positive contribution to the management of education in other educational institutions